Deformation induced martensite characterization in Fe-30%Ni-5%Cu alloy - Güler E.; Güler M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Deformation induced martensite properties were examined according to existing martensite morphology, crystallography and formation temperatures for different prior austenite homogenization conditions in Fe-30%Ni-5%Cu alloy. Scanning electron microscope (SEM), differential scanning calorimetry (DSC) and X-ray diffraction (XRD) techniques were employed to investigation. Scanning electron microscope observations showed elongated deformation induced martensite morphology in the austenite phase of alloy. As well, after deformation martensite start temperatures (Ms) were determined as -101°C and -105°C from DSC measurements for different homogenization conditions. In addition, X-ray diffraction analysis revealed the face centred cubic (fcc) of austenite phases and body centred cubic (bcc) deformation induced martensite phases for all studied samples.